Addressing and Improving Legal Development in the Economy Through a Case Study of the Increase in Hajj Pilgrimage Costs in Indonesia - Yenrizka Gusmaria; Tri Setiady (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Hajj pilgrimage is an important religious journey and must be carried out by all Muslims in the world and Indonesia has the largest Muslim population in the world. This research aims to analyze the development of the number of Hajj pilgrims in Indonesia in recent years and analyze the significant increase in Hajj costs after the Hajj pilgrimage was closed during the Covid-19 pandemic. In this research, the author uses statistical data to determine the development of Hajj pilgrims, the factors increasing the cost of the Hajj pilgrimage and the social and economic impact. The results of this research show that despite the increase in the cost of the Hajj pilgrimage, pilgrims still continue to increase compared to the previous year. One of the factors for the increase in Hajj pilgrims is due to the closure of access to the Hajj pilgrimage in 2020 to 2021, this is due to the Covid-19 pandemic. The impact of the pandemic has affected all countries' economies, one of the countries affected is Indonesia, because this significant change in the Indonesian economy has resulted in an increase in the cost of the Hajj. With the proposed increase in the cost of the Hajj pilgrimage every year, it is a form of understanding regarding legal and economic development in Indonesia. It can be said that if the law is unable to play an effective role, it will certainly have a negative impact on economic development.